Painting by Henri Martin in Charlier Museum, Brussels - Henri-Jean Guillaume... (Wikimedia Commons)
Notice iconographique issue de Wikimedia Commons. Titre: Painting by Henri Martin in Charlier Museum, Brussels. Painting in the Charlier Museum, Brussels
Droits : Licence Public domain via Wikimedia Commons
Keywords: œuvre d'art; tableau; sculpture; statue; wikimedia commons; Peintures